Expression of therapeutic levels of factor VIII in hemophilia A mice using a novel adeno/adeno-associated hybrid virus - Gnatenko, Dmitri V.; Wu, Yong; Jesty, Jolyon; Damon, Andrea L.; Hearing, Patrick; Bahou, Wadie F. (Thrombosis and Haemostasis, 2004)
We have generated an E1a/E1b/E3-deleted adeno/adeno-associated (Ad/AAV) hybrid virus driven by a small nuclear RNA (pHU1-1) promoter for expression of a B domain-deleted (Thr761-Asn1639) factor VIII transgene (FVIIIΔ761-1639). Productive replication of Ad/AAV/FVIIIΔ761-1639 in AAV repexpressing cells resulted in generation of monomeric and dimeric mini-adenoviral (mAd) replicative forms that retained the AAV integration elements (mAd/FVIIIΔ761-1639). In vitro studies using Ad/AAV/FVIIIΔ761-1639 generated ∼2-logs greater FVIII activity than mAd/FVIIIΔ761-1639. To determine its capacity for in vivo excision and/or genomic integration, Ad/AAV/FVIIIΔ761-1639 was injected by tail vein into three groups of hemophilia A mice (2 X 1011 vp [n = 3]; 4 X 1011 vp [n = 3]; 8 X 1011 vp [n = 3]), with clear concentration-dependent increase in FVIII activity (range 160-510 mU/ml; plasma activity 16% – 51% of normal). Peak activity was seen by Day (D) 5, with slow return to baseline by D28 (0.1 – 0.9% activity); in only 3/9 mice was loss of FVIII activity associated with development of anti-FVIII antibodies. Quantitative-PCR using genomic DNA isolated from D28 liver, spleen, heart, lungs, and kidney demonstrated the highest concentration in liver (∼10 genomes/ cell), with little to no organ toxicity at early (D5 or 6) or late (D28) post-infusion time points. There was no evidence for spontaneous transgene excision or genomic integration in vivo as evaluated by quantitative PCR and genomic blotting. These data establish (i) the feasibility and applicability of developing high-titer Ad/AAV hybrid viruses for FVIII delivery using a small cellular promoter, (ii) the potential utility of this virus for generation of “gutted” monomeric and dimeric mAD/FVIII retaining AAV integration elements, and (iii) that the development of strategies for regulated Rep68/78 co-expression may provide a novel approach for excision, integration, and long-term FVIII transgene expression.
Keywords: Gene therapy; haemophilia A; hybrid vector